The impact of gendered language in residency program descriptions on medical students' perceptions - Reagan E. Treadwell Smucker; Catherine G. Nguyen; Catherine E. Read; Jovanna A. Tracz; Laurie L. Wellman (Springer, 2024)
Abstract Background Medical students may be influenced by perceived program culture and personal fit when applying to residency. Activity Medical students were given three iterations of a generic residency program description presented with gender-neutral, feminine, or masculine skewed language and were subsequently asked to assess their perception of gender diversity and fit within each program. Results Gendered language in program descriptions had a direct effect on all participants' sense of gender diversity in programs. The feminine-skewed description was most favorably perceived, regardless of respondent gender. Conclusion These findings provide a starting point from which residency programs can consider the impact of gendered language on student recruitment and gender equity.